Use of concept maps as a tool to promote meaningful learning of concepts of optical phenomena in PROEJA - Freitas, Pedro Hiago de Melo (2012)
This article aims to verify the potential of constructing concept maps, using the computational tool CMap Tools, as a teaching tool and evaluative light of the theory ausubeliana for learning the concepts of optical phenomena. And a sample of students from the technical course in PROEJA Campus Buildings Teresina Central IFPI. The research method used was the Case Study, with the instrument using a questionnaire and concept maps. In analyzing the results, the use of concept maps as a cognitive tool, facilitates the learning process of the content optics, because it provides favorable conditions for the assimilation of knowledge, it remains more structured and organized in relation to the hierarchy of concepts in the content question.